Multimedia Interaktif Berbasis Games Edukatif guna Mengembangkan Kecerdasan Visual Spasial Anak Usia Dini di RA Muslimat NU Rowolaku - Dicky Anggriawan Nugroho; Dini Khanifatun Najah; Adillah Afni Labibah; Salwa Salsabila (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to develop the visual spatial intelligence of early childhood through interactive multimedia based on educational games at RA Muslimat NU Rowolaku, Kajen District. Visual spatial intelligence is essential in supporting a child's ability to understand shapes, colors, and spaces, which has a significant impact on their cognitive development. This research method is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed to see the impact of educational games on children's visual spatial abilities. The results of the study show that the use of interactive multimedia based on educational games effectively improves the visual spatial skills of early childhood. This is reflected in the improvement of children's ability to recognize shapes, arrange patterns, and improve skills in solving space-based problems. Educational games provide a more fun and interesting learning experience, so that they can motivate children to learn more creatively and interactively. Thus, interactive multimedia based on educational games can be an effective alternative method in the learning process in early childhood education institutions.